IMPACT OF CORPORATE SOCIAL RESPONSIBILITY O MARKET VALUE OF LISTED CONGLOMERATE COMPANIES NIGERIA - Kwache, Musa Bamaiyi; Mauda, Ahmed Bakari; Mohammed, Danjuma; Jerry, Musa Samuel (Kashere Journal of Management Sciences, 2025)
The study examines how corporate social responsibility affects Nigerian listed market value. Community engagement, Human Resource Management (HRM) disclosures, and charitable contributions are used to examine how CSR affects listed conglomerates’ market value in Nigeria. The study used panel data regression to determine how CSR affec company market value. The study population includes all five Nigerian stock exchange listed conglomerate companies as at December 31, 202 The study examines how corporate social responsibility affects Nigerian listed companies’ market value. Community engagement, Human Resource Management (HRM) disclosures, and charitable contributions are used to examine how CSR affects listed conglomerates’ market value in Nigeria. The study used panel data regression to determine how CSR affects company market value. The study population includes all five Nigerian stock exchange December 31, 2024. The study found that community based CSR initiatives negatively affect market value, while HRM disclosures have n However, charitable contributions boost market value in Nigerian conglomerates. The study recommends that these companies’ management take a more targeted and strategic approach to CSR implementation immediately. Strategic based CSR initiatives negatively affect market value, while HRM disclosures have no effect. However, charitable contributions boost market value in Nigerian conglomerates. The study recommends that these companies’ management take a more targeted and strategic approach to CSR implementation immediately. Strategic alignment and transparent communication of CSR initiatives to increase market value, strengthen local ties, and foster communication of CSR initiatives to increase market value, strengthen local ties, and foster business growth and financial performance.